2018
DOI: 10.2147/ijn.s178270
|View full text |Cite
|
Sign up to set email alerts
|

Inverse opal substrate-loaded mesenchymal stem cells contribute to decreased myocardial remodeling after transplantation into acute myocardial infarction mice

Abstract: BackgroundThe two-dimensional incubation method is now the most commonly method for mesenchymal stem cell (MSC) production. however, gene expression and secretion of growth factors are relatively low; thus, the transplanted cells cannot be effectively utilized for potential clinical applications after acute myocardial infarction (AMI).ObjectivesWe aimed to investigate whether our newly made substrates of inverse opal with specific surface microstructures for MSC culturing can increase the viability of the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Their transmembrane potential is eventually lost after significant cellular damage ( 27 ). Lu et al ( 28 ) has observed improvements in mitochondrial membrane potential in activated MSCs and this was associated with better therapeutic effects. We demonstrated that guarana, as well as caffeine, preserved mitochondrial membrane potential and that caffeine promoted a significant hyperpolarization.…”
Section: Discussionmentioning
confidence: 98%
“…Their transmembrane potential is eventually lost after significant cellular damage ( 27 ). Lu et al ( 28 ) has observed improvements in mitochondrial membrane potential in activated MSCs and this was associated with better therapeutic effects. We demonstrated that guarana, as well as caffeine, preserved mitochondrial membrane potential and that caffeine promoted a significant hyperpolarization.…”
Section: Discussionmentioning
confidence: 98%
“… ECM/silk proteins NPs [ 125 ] ADSCs with inverse opals n.a. Inverse opals [ 126 ] ADSCs with simvastatin NPs Simvastatin Polymer NPs [ 127 ] SPIO-ADSCs n.a. Superparamagnetic iron oxide NPs [ 128 ] IONP–MSC–derived NVs Extracellular nanovesicles n.a.…”
Section: Nanomedicine Mediated Therapeutics Strategies For MImentioning
confidence: 99%
“…Furthermore, Au@Pt/Alg hydrogel loaded with BASCs showed effective antioxidant and anti-inflammatory ability, enhanced the survival of implanted BASCs, and improved electrical conduction velocity and cardiac function, indicating the excellent ability of the hydrogel to promote cardiac repair. 14 In addition, melatonin-loaded PLGA‐mPEG nanoparticles, 124 chitosan-silk fibroin hydrogel incorporated with gold nanoparticles, 139 nanoparticles incorporated with ECM/silk proteins, 125 and inverse opals 126 were used to achieve higher ADSC survival rates in the infarcted areas and improve the therapeutic efficacy for MI treatment. In addition, ADSCs could also function as drug-delivery tools.…”
Section: Nanomedicine Mediated Therapeutics Strategies For MImentioning
confidence: 99%
“…(from C57BL/6 wild-type mice) were prepared as previously described [14]. The femurs and tibias of 6-week-old mice were first flushed with PBS (HyClone) to collect the bone marrow cells.…”
Section: Msc Preparation and Labeling Mouse-derived Mscsmentioning
confidence: 99%